The Strategi Kebijakan Pemerintah dalam Pengembangan Desa Wisata melalui BUMDES : Strategi Kebijakan Pemerintah dalam Pengembangan Desa Wisata melalui Badan Usaha Milik Desa - Elok Puri Maharani, Andina; Chandra Shasmita Haningati, Gumilang; Arsyi Dewangga, Muhammad (Mendapo: Journal of Administrative Law, 2024)
In Indonesia, the tourism sector is one of the field that supported community economic wellbeing. Development of tourism involve not only national scale but also local government which is the village. Development of tourism could be achieved through  Badan Usaha Milik Desa (BUMDES) which manifest in form of tourism village. However, there are several obstacles in the management of tourist villages implemented by BUMDES, including accessibility, difficulties in determining core BUMDES business activities, development strategies that only imitate trends, human resource factors and political factors. The development of tourist villages through BUMDES needs to pay attention to four important components including tourist attractions, availability of transportation, activities and tourist amenities.Based on this, the aim of this research is to explain how important it is to prepare a good planning program as stated in the regulations regarding Priority Use of Village Funds in 2023 based on Permendes Nomor 8 Tahun 2022 tentang Prioritas Penggunaan Dana Desa Tahun 2023. The method used in this research is Qualitative Descriptive, which focuses on the study of literature and legislation. The results of this Jurnal  research show that there are the inhibiting factors that cause tourist villages managedby BUMDES to not run smoothly.